Is determination of transition zone volume by transrectal ultrasound in patients with clinically benign prostatic enlargement sufficiently reliable in the clinical setting? - Szopinski, Tomasz (Termedia Publishing House, 2014)
INTRODUCTION: Controversies exist regarding the accuracy of transrectal ultrasound (TRUS) determination of transition zone volume (TZV) when compared with enucleated adenoma weight. AIM: To determine the accuracy and reliability of measurements of the TZV by TRUS, by comparing preoperative radiological findings with the enucleated prostate adenoma volume, measured by fluid displacement volumetry (FDV), after retropubic prostatectomy performed by the Millin method, and, moreover, to evaluate changes in the surgical capsule size in the intermediate postoperative period. MATERIAL AND METHODS: We measured TZV preoperatively using TRUS and postoperatively with FDV in 112 patients who underwent retroperitoneal prostatectomy for benign prostatic hyperplasia (BPH). RESULTS: The TRUS volume correlated well with specimen volumes (r = 0.945, p < 0.0001). The median (quartile 1, quartile 3) absolute error was 7.35 ml (4.15 ml, 9.28 ml) and the median percent error was 9.12% (4.75%, 14.98%). Percent error, but not absolute error, was significantly related to TRUS TZV (p < 0.001 and 0.217, respectively). Adenomas > 80 cc were associated with lower percent error. The median volume of the residual prostate tissue measured 3.5 years after prostatectomy was 92.65 cc (65.75 cc, 109.58 cc), whereas the median volume of the surgical capsule, depending on the equation used for its calculation, was 24.80 cc (16.25 cc, 37.37 cc) and 31.43 cc (23.14 cc, 43.32 cc). CONCLUSIONS: The TRUS TZV correlated well with values determined by FDV. It can be reliably used in clinical management of BPH.